The discovery of the subgenus Hysterobolus Viereck, 1913 (Hymenoptera, Braconidae, Brachistinae, Blacini, Blacus) in China, with description of nine new species - Lu, Qian-Yu; Achterberg, Cornelis Van; Tang, Pu; Chen, Xue-Xin (Zootaxa, 2023)
The subgenus Hysterobolus Viereck, 1913 (Hymenoptera, Braconidae, Blacus) is newly recorded from China. Nine new species are proposed, B. (H.) baishanzuensis sp. nov., B. (H.) flaviceps sp. nov., B. (H.) laculaticornis sp. nov., B. (H.) longiapicalis sp. nov., B. (H.) melanoapicalis sp. nov., B. (H.) niger sp. nov., B. (H.) variegatus sp. nov., B. (H.) xui sp. nov., B. (H.) yunnanensis sp. nov., and one species, B. (H.) chabarovi Belokobylskij, 1995, is newly recorded from China. An updated key to the currently known species of the subgenus Hysterobolus in China is provided.